Understanding Kratom Use: A Guide for Healthcare Providers - Swogger, Marc T.; Smith, Kirsten E.; Garcia-Romeu, Albert; Grundmann, Oliver; Veltri, Charles A.; Henningfield, Jack E.; Busch, Lorna Y. (Frontiers in Pharmacology, 2022)
Kratom (Mitragyna speciosa Korth., Rubiaceae) is a plant native to Southeast Asia, where it has been used for centuries as a mild stimulant and as medicine for various ailments. More recently, as kratom has gained popularity in the West, U.S. federal agencies have raised concerns over its safety leading to criminalization in some states and cities. Some of these safety concerns have echoed across media and broad-based health websites and, in the absence of clinical trials to test kratom’s efficacy and safety, considerable confusion has arisen among healthcare providers. There is, however, a growing literature of peer-reviewed science that can inform healthcare providers so that they are better equipped to discuss kratom use with consumers and people considering kratom use within the context of their overall health and safety, while recognizing that neither kratom nor any of its constituent substances or metabolites have been approved as safe and effective for any disease. An especially important gap in safety-related science is the use of kratom in combination with physiologically active substances and medicines. With these caveats in mind we provide a comprehensive overview of the available science on kratom that has the potential to i clarity for healthcare providers and patients. We conclude by making recommendations for best practices in working with people who use kratom.